2009
DOI: 10.1080/08039480802298705
|View full text |Cite
|
Sign up to set email alerts
|

Substance use disorders among personality disordered patients admitted for day hospital treatment. Implications for service developments

Abstract: Personality disorders (PD) and substance use disorders (SUD) are highly comorbid conditions. However, their treatment services are often separated. The aims of this study was to investigate how extensive this separation was prior to a Norwegian health reform (2004) that promoted integration, and to discuss clinical challenges for an integrated treatment of PD and SUD. All patients with a diagnosis of PD (n=1783) admitted to 10 day hospital treatment programs (1993-2003) were examined. Diagnoses were assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…BPD has been found as a significant risk factor for the persistence of SUD (Fenton et al, 2012 ), but remission of SUD in BPD in a 10-year study was also common (Zanarini et al, 2011). Treatment of patients with BPD/SUD has been described as difficult due to high dropout rates and to relational problems that make the process of establishing a therapeutic alliance challenging (Karterud, Arefjord, Andresen, & Pedersen, 2009).…”
Section: /30mentioning
confidence: 99%
“…BPD has been found as a significant risk factor for the persistence of SUD (Fenton et al, 2012 ), but remission of SUD in BPD in a 10-year study was also common (Zanarini et al, 2011). Treatment of patients with BPD/SUD has been described as difficult due to high dropout rates and to relational problems that make the process of establishing a therapeutic alliance challenging (Karterud, Arefjord, Andresen, & Pedersen, 2009).…”
Section: /30mentioning
confidence: 99%
“…SUD patients with co-occurring BPD are described as more resistant to entering into treatment, less compliant with treatment, and demonstrating high behavioral disinhibition associated with a subsequent return to heavy drug or alcohol use (Bradizza et al, 2006; Van Horn and Frank, 1998). Karterud et al (2009) found that patients being treated for personality disorders (including BPD) who were comorbid for an SUD displayed more aggression during treatment and dropped out more frequently. Both Shevlin et al (2007) and Thatcher et al (2005) have also demonstrated that AUDs (and mood and anxiety disorders) are strongly associated with a high BPD symptom class group (endorsement of more criteria).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have evaluated the efficacy of psychotherapy in patients with SUD and comorbid PD 9 – 11 are sparse and often controversial. 12 , 13 In contrast, a variety of different psychotherapeutic interventions have been proven effective for PD in several prospective studies, 14 – 16 and similar outcomes are achieved regardless of whether the interventions are applied in outpatient settings, 17 – 21 day hospital programs, 22 – 27 or inpatient programs. 28 However, many of the studies that have investigated the efficacy of PD psychotherapy have excluded PD patients with concurrent SUD (PD-SUD).…”
Section: Introductionmentioning
confidence: 99%